Developing healthy food for toddlers based on local purple sweet potato food - Node Siregar, Nova Sontry; Sihite, Helprida; Simamora, Mayes Felda (Institute of Computer Science (IOCS), 2025)
Nutritional issues in toddlers, particularly stunting, are crucial and align with the fourth point of Asta Cita (Association of Indonesians), namely improving the quality of life of the Indonesian people. This condition not only impacts children's height but also their cognitive development, productivity, and the long-term quality of human resources. To address this, innovation is needed to meet the nutritional needs of toddlers through the use of readily available and nutritious local foods. One potential local food that can be utilized is purple sweet potatoes. Purple sweet potatoes contain natural antioxidants (anthocyanins), vitamins A, C, and E, and dietary fiber, which are good for supporting growth and strengthening children's immune systems. This study aims to provide alternative local food ingredients that are highly nutritious and acceptable, readily available, and easy to process by the wider community. This study used a quasi-experimental design with a one-group pretest-posttest design on mothers of toddlers. The study variables were knowledge and skills, which were measured twice: before and after the purple sweet potato processing practice. The results showed a significant difference. (2-tailed) at knowledge 0.000 < 0.05 and skills significance value 0.000 < 0.05 then there is a significant difference between knowledge and skills before and after the purple sweet potato processing practice. The conclusion is that the purple sweet potato processing practice is effective in increasing the knowledge and skills of mothers of toddlers. The implication is that similar educational or training programs can be implemented more widely in the community to improve mothers' ability to provide nutritious food for their toddlers